BER Performance Analysis Over AWGN Channeling For GFSK Modulation To Transmitting Unstructured Data - Nanang Cahyadi (Journal of Informatics and Communication Technology (JICT), 2022)
The first step to enable the optimize the use of information exchange radio-based could be started by providing research on supporting devices. Research on supporting devices and their application, especially in providing service to exchange text-based information is crucial and opens up chances to solve the rest challenges such as signal power, data transfer speed, and security. This research aims to evaluate signal behavior from design information text-based exchange using radio transmission. To achieve the goal, this research adopts a quantitative methodology by comparing theoretical results and simulation results of the design. tuning samples per symbol could give better BER with lower EbNo. The data also demonstrated great results that show using 2 samples per symbol could deliver the best performance that has lower BER and lowest EbNo compared to the rest of the data, including the estimated BER using coherent FSK. It affects the GFSK signal not only very smoothly compared to the FSK signal, but also being able to achieve a minimum BER with the IEEE standard without requiring excessive energy by simply setting samples per symbol at 2. This can be seen from the results of BER 10-3 with energy EbNo was 6.5 dB.